2005
DOI: 10.1038/sj.onc.1208527
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of specific protein expression levels by PTEN: identification of AKAP121, DHFR, G3BP, Rap1 and RCC1 as potential targets of PTEN

Abstract: The tumor suppressor PTEN is mutated in a high percentage of human cancers, and is implicated in pathways regulating cell growth, proliferation, survival, and migration. Despite significant advances, our understanding of its mechanisms of action remains incomplete. We have used a high-throughput proteomic immunoblotting approach to identify proteins whose expression levels are modulated by PTEN. Out of over 800 proteins screened, 22 proteins showed significant changes in expression. Five proteins that exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…7C). This would be consistent with recent reports demonstrating selective regulation of protein stability by PTEN (13) and Akt (33). We are currently assessing this possibility.…”
Section: Discussionsupporting
confidence: 78%
“…7C). This would be consistent with recent reports demonstrating selective regulation of protein stability by PTEN (13) and Akt (33). We are currently assessing this possibility.…”
Section: Discussionsupporting
confidence: 78%
“…Finally, it has been shown that PTEN interacts with a variety of molecules that have been associated with cell growth, apoptosis, and cell cycle control (33,34). Studies designed to define the PTEN interactome in response to ␣2␤1 integrin-type I collagen interaction will probably shed further light on the mechanism by which collagen matrix contraction modulates PTEN activity.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of G3BP1 was noted in PTEN-null human cells, whereas overexpression of PTEN suppressed G3BP1 expression. Furthermore, the negative effect of PTEN expression on G3BP1 protein levels was recapitulated by direct inhibition of PI3 kinase activity (Huang et al, 2005). G3BP1 levels have also been shown to increase in response to heregulin in human Her2-positive breast cancer cells (Barnes et al, 2002).…”
Section: Introductionmentioning
confidence: 99%